2019
DOI: 10.1002/cam4.2221
|View full text |Cite
|
Sign up to set email alerts
|

How to choose proper local treatment in men aged ≥75 years with cT2 localized prostate cancer?

Abstract: Background For localized prostate cancer (PCa), radical prostatectomy (RP) and radiotherapy (RT) are two standard interventions to decrease PCa mortality. Contemporary studies contained the elderly people; analyses focusing on patients over 75 years of age were still lacking. Method In the Surveillance Epidemiology and End Results (SEER) database (2004‐2015), people over 75 years of age with cT2 stage were selected in our research. Multivariable Cox proportional hazard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Because the treatment method mainly targets the patients' special parts through the urinary system surgery, patients are prone to greater psychological burdens. erefore, a scientific psychological intervention mode is more conducive to the postoperative rehabilitation of patients [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Because the treatment method mainly targets the patients' special parts through the urinary system surgery, patients are prone to greater psychological burdens. erefore, a scientific psychological intervention mode is more conducive to the postoperative rehabilitation of patients [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there are no RCTs evaluating the comparison of treatments in an elderly population. Notably, one large retrospective study including 10,563 men aged ≥75 years with cT2 localized PCa showed that RP was superior to RT in overall survival and cancer-specific survival after propensity score matching (hazard ratio (HR) = 0.54, 95% confidence interval (CI) = 0.47–0.62, and HR = 0.30, 95% CI = 0.20–0.45) [ 25 ]. Interestingly, a sub-analysis in the study showed that for patients with Gleason score (GS) = 7, RP provided a higher risk decline of overall death when compared with RT treatment [ 25 ].…”
Section: Surgical Tolerability In ‘Elderly’ Patientsmentioning
confidence: 99%